Evaluating commercialisation models in the water supply sector: a comparative case analysis of LWSC, Aguas Andinas and Johannesburg Water (2001-2014) - Banda, Ason (Research of GSB, 2018)
Most people in developing countries lack access to clean water, which leads to water-related diseases. The water supply challenges in many developing countries have persisted despite the water sector receiving considerable amount of support from the international organisations and cooperating partners. In this study I analysed different water reforms undertaken in developing market economies with a specific focus on Chile, South Africa and Zambia. The main research question I sought to address is whether commercialisation has proportionately improved water supply delivery in the aforementioned countries. The research employs a qualitative comparative case study approach of three Commercial Utilities (CUs), namely Lusaka Water and Sewerage Company (LWSC), Johannesburg Water and Aguas Andinas. Performance improvement was assessed using selected indicators under four broad criteria; accessibility, reliability, affordability and profitability for the period 2001 to 2014. The significant finding is that all CUs with different reform models had improved performance after commercialisation which is attributed to adoption of market principles and good corporate practices. The research established that private service delivery with strong state involvement outperformed public service delivery in terms of efficiency, accessibility, reliability and affordability. Privatised Aguas Andinas exhibited the highest level of performance in terms of accessibility, reliability, profitability and affordability. Johannesburg Water performed better than LWSC in terms of accessibility and reliability while LWSC performed better than Johannesburg Water in terms of affordability and profitability across the period 2001 to 2014. LWSC improved service in terms of accessibility, reliability, affordability and operational efficiency after corporatisation. The main conclusion is that even though Aguas Andinas has exhibited the highest level of performance, the strong performance is attributed to strong state involvement, tariff and subside systems, legal and institutional systems, management skills, sound corporate governance, customer orientation and innovation. Therefore, all the three models; privatisation, corporatisation and management contract, are suitable models for developing economies provided the state play its role and CUs adopt best practices.